(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
Overactive bladder syndrome encompasses a series of symptoms that are both bothersome for the patient and, in most cases, serious from a medical perspective. The investigations protocol ranges from basic to very complex, yet, the treatment alternatives are limited, mainly due to insufficient efficacy or poor tolerability. Sacral neuromodulation promises to do for the bladder what a peacemaker does for the cord, which is regulating normal activity and preventing abnormal behavior. Our paper reviews the current state of the art regarding the overactive bladder, focusing on neuromodulation, its principle, indications, and known limits. Data from the literature is analyzed and presented in an analytical fashion. We conclude that this is a promising treatment alternative although limited by price, difficult implantation technique, and unpredictable efficacy.